Electricity consumption and foreign direct investment: Empirical evidence from Indonesia - Putri Khairani, , (2017)
Over the last three decades, most of developing countries pay more attention to foreign direct investments (FDI) activities, at both national and international level. Economists believe that FDI is one of the most important sources of globalization and an important catalyst for economic growth, especially for the developing countries. FDI can be one of the sources of capital to stimulate the economy of the country, as well as a contributor to the national development through the transfer of an asset, generators of employment, high productivity, competitiveness, management, and technology spillovers. However, deficiency in quality and a limited quantity of electricity is one of the issues that remains a perpetual bugbear that hampering Indonesia’s economic and social development. The objective of this study is to investigate whether electricity consumption affects the inflow of FDI in Indonesia. The analysis is based on Autoregressive Distributed Lag (ARDL) model using time series annual data from 1980-2016 of FDI, electricity consumption, and other macroeconomic variables such as GDP, exchange rate, openness, labor force, and education expenditure as control variables. Using various econometric techniques like Unit Root Test, Bounds Test, Cointegrating and long-run test and Granger causality test, it was found that there are a long-run relationship and positive correlation between electricity consumption and FDI in Indonesia. However, Granger causality result shows that there is no causality running from FDI to electricity consumption and vice versa.